MonoMac syndrome with associated neurological deficits and longitudinally extensive cord lesion. (21st April 2018) - Monif, Mastura; Huq, Aamira; Chee, Lynette; Kilpatrick, Trevor
Abstract : We present a case of monocytopaenia and mycobacteria-related infection (MonoMac) syndrome in a 30-year-old man of Indian origin. The clinical diagnosis of GATA2 haploinsufficiency was suspected after an unusual neurological presentation on a background of myelodysplastic syndrome and childhood pulmonary tuberculosis. The patient had a longitudinally extensive spinal cord lesion and a lesion in the medulla. No obvious infective cause for the spinal cord MRI abnormality was found, and the lesions were presumed to be inflammatory in nature. The family history consisted of autosomal dominant clinical features suggestive of GATA2 haploinsufficiency. Genetic testing in peripheral leucocytes revealed a pathogenic mutation in GATA2 . This is the first-ever published case of possible MonoMac syndrome with a neurological presentation. The case highlights the rarity and complexity of the diagnosis and the clinical sequelae that ensued with the patient dying of gram-negative septicaemia while receiving intravenous steroid therapy for the spinal cord lesion.